Touch sensation as part of multimedia design elements to improve computer accessibility for the blind users - Muniandy, M. (IEEE Computer Society, 2017)
Many HCI researchers are keen in producing accessible computer applications for the users. However, not many of these findings focus on disable user especially the blind. Most of the technological advancement meant for the blind user is in the form of assistive technologies mainly screen reader. Blind user has highlighted the inefficiency of screen reader as well as other unobtainable and expensive assistive technologies. This paper proposes the use of touch sensation as one of the essential design element to exist alongside with other multimedia design elements. A prototype was developed incorporating the multimedia design elements and was tested among blind users to measure the usability score. The result indicates that touch sensation plays an important role in improving the representation of a computer application to blind. Associating touch sensation in improving the accessibility of computer application has produced totally new experience to the blind users in perceiving information thus enhanced the learning process altogether. © 2017 IEEE.